Analyses on Flavonoids and Transcriptome Reveals Key MYB Gene for Proanthocyanidins Regulation in Onobrychis Viciifolia - Jin, Zhongzhiyue; Jiang, Wenbo; Luo, Yijing; Huang, Haijun; Yi, Dengxia; Pang, Yongzhen (Frontiers in Plant Science, 2022)
Onobrychis viciifolia (sainfoin) is one of the most high-quality legume forages, which is rich in proanthocyanidins that is beneficial for the health and production of animals. In this study, proanthocyanidins and total flavonoids in leaves of 46 different sainfoin germplasm resources were evaluated, and it showed that soluble proanthocyanidin contents varied greatly in these sainfoin germplasm resources, but total flavonoids did not show significant difference. Transcriptome sequencing with high and low proanthocyanidins sainfoin resulted in identification of total 52,926 unigenes in sainfoin, and they were classed into different GOC categories. Among them, 1,608 unigenes were differentially expressed in high and low proanthocyanidins sainfoin samples, including 1,160 genes that were up-regulated and 448 genes that were down-regulated. Analysis on gene enrichment via KEGG annotation revealed that the differentially expressed genes were mainly enriched in the phenylpropanoid biosynthetic pathway and the secondary metabolism pathway. We also analyzed the expression levels of structural genes of the proanthocyanidin/flavonoid pathway in roots, stems and leaves in the high proanthocyanidin sainfoin via RT-qPCR, and found these genes were differentially expressed in these tissues. Among them, the expression levels of F3'5'H and ANR were higher in leaves than in roots or stems, which is consistent with proanthocyanidins content in these tissues. Among MYB genes that were differentially expressed, the expression of OvMYBPA2 was relatively high in high proanthocyanidin sainfoin. Over-expression level of OvMYBPA2 in alfalfa hairy roots resulted in decreased anthocyanin content but increased proanthocyanidin content. Our study provided transcriptome information for further functional characterization of proanthocyanidin biosynthesis related genes in sainfoin, and candidate key MYB genes for bioengineering of proanthocyanidins in planta.